2010
DOI: 10.1111/j.1440-1746.2010.06556.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal: Sigmoidocecal fistula diagnosed with colonoscopy

Abstract: Gastrointestinal: Sigmoidocecal fistula diagnosed with colonoscopyA 42-year-old woman underwent a colonoscopy for evaluation of abdominal bloating of three months' duration. Colonoscopic view revealed a large collapsed fistulous opening of the sigmoid colon. The ileocecal valve was identified when the colonoscope was passed through the fistulous opening connecting with the sigmoid colon. When the colonoscope reached the cecum through the conventional intra-luminal technique, white numbers corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has also been suggested that duodenal bile salts have an irritating effects on colonic mucosa resulting in diarrhea. However, colo-colonic fistulas usually have insidious presentation with nonspecific symptoms [7]. Diarrhea and rectal bleeding were the most common symptoms seen in our patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It has also been suggested that duodenal bile salts have an irritating effects on colonic mucosa resulting in diarrhea. However, colo-colonic fistulas usually have insidious presentation with nonspecific symptoms [7]. Diarrhea and rectal bleeding were the most common symptoms seen in our patients.…”
Section: Discussionmentioning
confidence: 61%
“…It has been shown that colo-colonic fistulas are usually a complication of inflammatory or neoplastic process. Sigmoido-cecal fistula, most probably as a complication of sigmoid diverticulitis, has been reported in a few case reports [7]. There was only one paper showing ceco-sigmoidal fistula caused by adenocarcinoma of the cecum [8].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Hyun et al referred to the diagnostic tools that are helpful in this uncommon complication. They recommended radiologic studies with contrast media, abdominal CT and colonoscopy combined with chromoendoscopy [10]. It is true that all of the aforementioned modalities can be useful in the diagnosis of sigmoido-cecal fistula, depending, however, on the clinical status of the patient and the manifestation of her or his disease.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a thorough search of the English literature, only a few cases of sigmoidocecal fistula due to sigmoid diverticulitis or inflammatory bowel disease were found. 5,6 These abnormal bowel communications, including colocolic fistula, gastrocolic fistula, or jejunocolic fistula, may lead to bacterial overgrowth. of lactulose.…”
Section: Discussionmentioning
confidence: 99%